Transfers from intensive care unit to hospital ward: a multicentre textual analysis of physician progress notes - Brown, Kyla N; Leigh, Jeanna P; Kamran, Hasham; Bagshaw, Sean M; Fowler, Rob A; Dodek, Peter M; Turgeon, Alexis F; Forster, Alan J; Lamontagne, Francois; Soo, Andrea; Stelfox, Henry T (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Little is known about documentation during transitions of patient care between clinical specialties. Therefore, we examined the focus, structure and purpose of physician progress notes for patients transferred from the intensive care unit (ICU) to hospital ward to identify opportunities to improve communication breaks. Methods This was a prospective cohort study in ten Canadian hospitals. We analyzed physician progress notes for consenting adult patients transferred from a medical-surgical ICU to hospital ward. The number, length, legibility and content of notes was counted and compared across care settings using mixed-effects linear regression models accounting for clustering within hospitals. Qualitative content analyses were conducted on a stratified random sample of 32 patients. Results A total of 447 patient medical records that included 7052 progress notes (mean 2.1 notes/patient/day 95% CI 1.9–2.3) were analyzed. Notes written by the ICU team were significantly longer than notes written by the ward team (mean lines of text 21 vs. 15, p < 0.001). There was a discrepancy between documentation of patient issues in the last ICU and first ward notes; mean agreement of patient issues was 42% [95% CI 31–53%]. Qualitative analyses identified eight themes related to focus (central point – e.g., problem list), structure (organization, – e.g., note-taking style), and purpose (intention – e.g., documentation of patient course) of the notes that varied across clinical specialties and physician seniority. Conclusions Important gaps and variations in written documentation during transitions of patient care between ICU and hospital ward physicians are common, and include discrepancies in documentation of patient information.